Permissibility of Advance Payment in Online Sales: An Analysis Studi of Fiqh Muamalah - Atiqah, Nur; Hervina, Hervina; Sofyan, Akhmad; Bah, Robiah (Ghaly: Journal of Islamic Economic Law, 2024)
This article discusses online buying and selling, especially contracts. The author found several consumers who carried out the buying and selling. This research aims to find out the practice of paying at the beginning of a transaction in online buying and selling and how Fikih Muamalah reviews this practice. Type of normative, empirical research with qualitative descriptive analysis. The respondents of this research were 21 consumers who made payments in advance for online buying and selling in the Loa Janan Ilir sub-district. The data collection techniques used by the author are observation, interviews, and documentation. The data analysis technique used is data management from interviews, documentation, and literature using qualitative descriptive analysis patterns.The results of this research obtained: first, the practice of payment at the beginning of transactions in online buying and selling in the community in Loa Janan Ilir sub-district is carried out by buyers ordering goods in the online shop application and stating the specifications of the desired goods and making payment immediately in advance according to the stated price. In the visual depiction, it is to be noted that the total cost encompasses not only the item's price but also the shipping charges. Furthermore, it must be noted that the dispatch of the goods in question will be deferred for several days before their shipment. Second, people in Loa Janan Ilir often buy and sell online using greeting contracts. Where payment must be made immediately for something that is still pending. This is permitted by some scholars as long as it does not conflict with Sharia law‟ applicable. However, some scholars do not allow this buying and selling because it is considered detrimental to one party. The seller must state in detail the details of the goods being sold to avoid elements of fraud.